Tinjauan Visual Promosi Pariwisata untuk Pengembangan Budaya Betawi di Jakarta - Ariani Kusumo Wardhani; Edi Chandra; Muhammad rafi Agustina (Gondang: Jurnal Seni dan Budaya, 2020)
The purpose of this study is to analyze the Betawi Culture promotional media that has been carried out by the DKI Jakarta Provincial Tourism and Culture Office and to find out the visualization needed for the development of Betawi Culture promotion in the future. A review of the existing Betawi Culture promotional media was carried out to analyze tourism promotion media through a visual review that has been carried out by the DKI Jakarta Provincial Tourism and Culture Office in developing Betawi culture for tourism promotion. The problem is focused on the Betawi tribe, which is the original ethnic group of the people of Jakarta. In order to approach this problem, a visual theory reference is used to analyze the promotional media that has been carried out by the Ministry of Tourism and Culture of DKI Jakarta. The data were collected by conducting a survey of respondents and interviews. Furthermore, descriptive qualitative analysis was carried out using visual media theory. Based on the results of the research, it shows that the Jakarta City Government Tourism and Culture Office has carried out tourism promotion activities by conducting promotions in print and digital media